New species of Gamasellodes Athias-Henriot and Zerconopsis Hull (Mesostigmata: Ascidae) from Colombia, with a complement to a recently published key to the world species of Gamasellodes, and with a key to the world species of Zerconopsis - Cobo, Nora Cristina Mesa; Abo-Shnaf, Reham I.A.; Ruedaramirez, Diana Marcela; De Castro, Luiz A.S. [UNESP]; De Moraes, Gilberto J. (Systematic and Applied Acarology Society, 2021)
Gamasellodes unalpalmi Mesa, Abo-Shnaf & Rueda-Ramirez sp. nov. and Zerconopsis zumbambicae Mesa, Abo-Shnaf & Rueda-Ramirez sp. nov. are described based on the morphology of adults obtained from litter and soil samples collected at Valle del Cauca province, Colombia. A complement to a recently published key to the world species of Gamasellodes and a key for the separation of females of the 18 recognizable world species of Zerconopsis are provided.
Keywords: predaceous mites.; soil mites; taxonomy